Second-Order Devolution Revolution and the Hidden Structural Discrimination? Examining County Welfare-to-Work Service Systems in California. Issue 5 (18th September 2020) - Chang, Yu-Ling; Lanfranconi, Lucia Marina; Clark, Kevin
ABSTRACT: Drawing from Critical Race Theory (CRT), and a structural intersectionality framework, we examine intersecting structural inequalities embedded in county welfare-to-work (WTW) service delivery in California. Using a mixed-method analytic approach, our results reveal that second-order-devolution revolution (SODR) shapes intersecting gender, racial, class, and spatial inequalities, and reproduces white supremacy. We find that counties with multiple privileged socioeconomic characteristics operate employment - or training-oriented WTW systems, whereas counties with multiple disadvantaged socioeconomic characteristics operate sanction - or education-oriented WTW systems. We discuss policy solutions to address the disparities in WTW service delivery systems.